Experiences from the Ruins of Everyday Life - Zaronskis, Tadas (Scenari, 2023)
In this article we treat the question of the subjective everyday life experience in T. W. Adorno’s philosophy. It is in no way evident how such experience can be central or even valuable for a critical knowledge of society, especially for Adorno, who tends to emphasize the illusory, ideological and damaged character of the “everyday life”. Nevertheless, his Minima Moralia (1951) is famously written “from the standpoint of subjective experience”. It is for this reason that Minima Moralia is in the center of our interrogations. In order to treat the epistemological problem pertaining to the role of subjective everyday life experience in Adorno’s critical theory of society, we proceed by numerous detours which elucidate surrounding and relating concepts, such as dissolution of the subject, objectivity of historical movement, domination. We conclude that Adorno’s concept of experience is itself marked by a fundamental split: an unstable and always fragile division between relapsing into ideology or becoming a reflection upon its own being damaged and virtually blocked. Subjective experience contributes to the objective knowledge of society by becoming consciousness of its own mutilation, and this because the reasons as much as the forms of this mutilation are objective, social.